Twenty thousand roads : women, movement, and the West - Scharff, Virginia (University of California Press, 2003)
From Sacagawea's travels with Lewis and Clark to rock groupie Pamela Des Barres's California trips, women have moved across the American West with profound consequences for the people and places they encounter. Virginia Scharff revisits a grand theme of United States history--our restless, relentless westward movement--but sets out in new directions, following women's trails from the early nineteenth to the late twentieth centuries.